Effects of different feeds on the population growth and protein content of mysids (metasiriella kitoral) - Aaron-Taleon, Guia T. (Iloilo University of the Philippines in the Visayas, College of Fisheries, 1991)
A study was conducted to determine the effect of rice bran, fish meal, acetes and chicken manure on the population and protein content of mysids (Metasiriellakitaroi). Mysids collected in brackishwater ponds stocked in large basins (16 org/1) reproduced after one weekwith a population count of 38 org/l in rice bran, 63 org/l. There was a decline in the population at harvest in all treatments. Analysis of variance on population showed no significant difference between treatment (P>.05) and no significant difference between trials (P>.05). For trial I, the protein content of mysids is basins during the mid culture period was 41.09% in ricebran ; 26.75% in fish meal ; 32.73 in acetes ; and 51.33% in chicken manure. In tanks, protein content obtained was 59.62% in rice bran ; 47.19% in fish meal ; 54.19% in acetes ; and 51.10% in chicken manure. Trial II resulted in a protein content of 72.32% in rice bran ; 63.19% in fish meal ; 44.42% in acetes ; 64.67% in chicken manure. At harvest, protein content of mysids onall treatments and all trials have decreased except for mysids fed with acetes in Trial II which has gained protein content (56.11%). Analysis of variance on population showed no significant difference between treatments (P>.05) and no significant difference between trials (P>.05). Correlation analysis on population and water parameters showed a highly significant correlation on [population and salinity during trial I (P=000) and a slight correlation between population and NH3-N in basins (P=.004). Temperature, dissolve oxygen and pH have no correlation to mysids population.
Thesis (M.S. Fisheries-Aquaculture) -- University of the Philippines in the Visayas, May 1992.